COMPARATIVE STUDY OF MADHU UDAK AND KOSHNA JALA AS ANUPANA IN STHAULYA - Subhash Ingale, Seema; Nandanikar, Ajit (International Journal of Ayurveda and Pharma Research, 2015)
Today, the world is reeling on the verge of an epidemic. This epidemic also termed as the New World Syndrome, which houses a cluster of non-communicable diseases is called as Obesity. Koshna Jala and Madhu Udak, both have Kaphashamak activity and predominantly act on Meda dhatu. Thus, the need to explore their role as Anupan for the Yog comprising of Triphala, Musta and Vidanga. Aim of the Study: To compare the effect of Madhu Udak and Koshna Jala as Anupan along with Triphala, Vidanga and Musta as combination in subjects of Sthaulya. Objective of Study: To understand and explain precisely the concept of Anupan. Type of Study: Randomized controlled clinical trial. Plan of Clinical Trial: The total number of subjects were 60. Investigations: Investigations were done before starting the treatment. Statistical Analysis: Paired & unpaired t-test & Wilcoxon - matched - pairs Signed - ranks test- were used for statistical analysis. Conclusion: Triphala, Vidanga and Musta given to the Sthaulya patients for 12 week which showed significant reduction in weight and other symptoms which is proved highly significant statistically. Both the Anupan Madhu Udak & Koshna Jala were effective but Madhu udak was found to be more effective.